Using PepExplorer to Filter and Organize De Novo Peptide Sequencing Results. Issue 1 (3rd September 2015) - da Veiga Leprevost, Felipe; Barbosa, Valmir C.; Carvalho, Paulo Costa
Abstract: PepExplorer aids in the biological interpretation of de novo sequencing results; this is accomplished by assembling a list of homolog proteins obtained by aligning results from widely adopted de novo sequencing tools against a target‐decoy sequence database. Our tool relies on pattern recognition to ensure that the results satisfy a user‐given false‐discovery rate (FDR). For this, it employs a radial basis function neural network that considers the precursor charge states, de novo sequencing scores, the peptide lengths, and alignment scores. PepExplorer is recommended for studies addressing organisms with no genomic sequence available. PepExplorer is integrated into the PatternLab for proteomics environment, which makes available various tools for downstream data analysis, including the resources for quantitative and differential proteomics. © 2015 by John Wiley & Sons, Inc.